2015
DOI: 10.5152/akd.2015.5930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy drinks on blood pressure, heart rate, and electrocardiographic parameters: An experimental study on healthy young adults

Abstract: Objective:To evaluate the effects of the consumption of energy drinks on cardiovascular parameters in a group of healthy young individuals.Methods:In a quasi-experimental study, 44 healthy adult participants aged between 15 and 30 years were evaluated. The blood pressure (BP) as well as electrocardiographic indices, including heart rate (HR), PR interval, QRS duration, corrected QT (QTc) interval, and ST-T changes were recorded before consumption of a caffeine-containing energy drink and at the specific time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 33 publications
3
50
1
Order By: Relevance
“…Differential acute cardiovascular responses across the various studies could also result from differences in the volume of the ED ingested, thereby reflecting differences in the water load, as well as in the amount of active ingredients consumed (Table 2). Indeed, the 30% lesser volume of the EDs used in the study by Ragsdale et al (31) and Hajsadeghi et al (38) than that used in our study (250 compared with 355 mL) could have contributed to the lack of a significant increase in blood pressure measured over 120 min. Furthermore, although in the study by Worthley et al (32) 250 mL of a sugar-free ED was found to elevate mean blood pressure at 60 min postconsumption, the increase in mean blood pressure (;3.5 mm Hg) was less than that observed at the same time point in our study with 355 mL of Red Bull (;5 mm Hg at 60 min postconsumption) (17).…”
Section: Eds and Hemodynamics: Discrepancies Between Studiescontrasting
confidence: 48%
See 3 more Smart Citations
“…Differential acute cardiovascular responses across the various studies could also result from differences in the volume of the ED ingested, thereby reflecting differences in the water load, as well as in the amount of active ingredients consumed (Table 2). Indeed, the 30% lesser volume of the EDs used in the study by Ragsdale et al (31) and Hajsadeghi et al (38) than that used in our study (250 compared with 355 mL) could have contributed to the lack of a significant increase in blood pressure measured over 120 min. Furthermore, although in the study by Worthley et al (32) 250 mL of a sugar-free ED was found to elevate mean blood pressure at 60 min postconsumption, the increase in mean blood pressure (;3.5 mm Hg) was less than that observed at the same time point in our study with 355 mL of Red Bull (;5 mm Hg at 60 min postconsumption) (17).…”
Section: Eds and Hemodynamics: Discrepancies Between Studiescontrasting
confidence: 48%
“…It is well established that posture has a significant impact on blood pressure variables and heart rate in a resting condition (42)(43)(44), as well as in responses to specific cardiovascular maneuvers (44), an effect that was suggested to be caused by changes in the intrathoracic blood volume (44). A recent publication investigated the cardiovascular impact of an ED in young healthy subjects and observed that heart rate was significantly lower at 30 and 120 min postconsumption than at baseline levels (38). In this study, heart rate was measured discontinuously at 30, 120, and 240 min postconsumption by using a Cardioline AR1200 with the subject in a supine position, whereas blood pressure variables were measured in a sitting position after a resting period of 5 min, which indicates a change in body posture between heart rate and blood pressure measurements (38).…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cardiovascular effects, such as supraventricular tachycardia, long QT syndrome, or myocardial infarction, have also been described after ED intake [2629]. In addition, a number of investigations have focused on the hemodynamic effects and endothelial functions of the consumption of energy drinks [3033]. For this reason we hypothesize that the complication described in our patient could be multifactorial and not only related to antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 75%